Leishmaniasis in Humans and Animals: A One Health Approach for Surveillance, Prevention and Control in a Changing World - Claudia Cosma; Carla Maia; Nushrat Khan; Maria Infantino; Marco Del Riccio (Tropical Medicine and Infectious Disease)
Leishmaniasis is classified as a neglected tropical disease (NTD), caused by protozoan parasites of the genus Leishmania, which are transmitted to humans and other animals through the bite of infected female phlebotomine sandflies. There are three forms of the disease: cutaneous leishmaniasis (CL) manifested by ulcers and scars; systemic or visceral leishmaniasis (VL), which can lead to life-threatening complications if left untreated; and mucocutaneous leishmaniasis (MCL), which can destroy the mucous membranes of the nose, mouth and throat. Human leishmaniasis is endemic in many countries across Africa, Asia, Southern Europe, the Middle East, and Central and South America. The interconnection of environmental, animal and human health underlies the spread of the Leishmania parasite. Environmental disruptions, such as climate change, deforestation or urbanisation, but also globalisation and migration, significantly affect the distribution and abundance of sand fly vectors and reservoir hosts. Climate change alters the breeding patterns of sandflies and expands their geographic range; deforestation and misuse of large areas disrupt ecosystems, leading to increased human-vector contact; and urbanisation increases the potential for contact between parties, particularly in densely populated areas. Migration of humans and animals, either through natural migration or, for example, the pet trade and breeding, can facilitate the spread of Leishmania parasites. In addition, socio-economic factors, including poverty and lack of access to healthcare, increase the burden of leishmaniasis in vulnerable populations. Due to this multitude of reasons, the geographic distribution of sandflies has expanded to higher latitudes and altitudes in recent years, with a consequent increase in disease burden. Indeed, despite ongoing challenges in the surveillance systems, data from the last available year have shown an increase in many cases in both humans and dogs. This perspective explores the interconnected factors influencing the spread of leishmaniasis worldwide and the epidemiology of the disease. In addition, it illustrates the importance of integrated strategies in a One Health approach: surveillance, prevention and control of vectors, animals and humans.